Modeling and Experimental Analysis of Grinding Surface Roughness of Face Gear - Ming Xingzu; Gao Qin; Xiao Lei; Long Yu; Liu Jinhua (Jixie chuandong)
The mathematical model of face gear grinding disc wheel is established according to the gear tooth surface formation mechanism analysis of surface roughness and morphology analysis of the disc wheel surface. Then,according to the grinding mechanism of face gear in the CNC gear grinding machine,the in- depth analysis of grinding movement relation between disc wheel and face gear is carried out,and the locus equation of grinding wheel abrasive cutting blade coordinate system is established,and then the M file is compiled to calculate the influence of different parameters on surface roughness value. By comparing calculation values with measured values,the maximum error in 11. 7%,the results show that the roughness model calculation values and measured values are basically identical.